A Correlation between Structural Parameters and Electrical Conductivity of Calcium‐Modified Ba(Zr0.05Ti0.95)O3 Ceramic - Selvamani, Rachna; Singh, Gurvinderjit; Tiwari, Vidya Sagar; Karnal, Ashwani K. (physica status solidi (b), 2021)
Lead‐free (Ba1–xCax)(Zr0.05Ti0.95)O3 (x = 0.03, 0.05, 0.08, 0.10, 0.12, and 0.15) (BCZTx) ceramics are fabricated using the solid state reaction method. The ionic conductivity of the ceramic samples is investigated by complex impedance spectroscopy. The impedance measurements suggest that doubly charged oxygen vacancies (VO··) are responsible for conduction and relaxation. The impedance measurements show that with increase in calcium content the ionic conductivity increases till x = 0.10 and thereafter it decreases gradually. This anomaly in the conductivity is discussed on the basis of structural parameters such as lattice free volume, tolerance factors, and number of equivalent oxygen sites. The presence of the anomaly at x = 0.10 is attributed to a balance between the number of equivalent oxygen sites increasing and the lattice free volume reducing with calcium content. The correlation of structural parameters such as lattice free volume, tolerance factors, and number of equivalent oxygen sites with ionic conductivity is investigated for (Ba1–xCax)(Zr0.05Ti0.95)O3 [x = 0.03, 0.05, 0.08, 0.10, 0.12, and 0.15] ceramic. The ionic conductivity increases till x = 0.10 and thereafter it decreases gradually. The presence of the anomaly at x = 0.10 is attributed to a balance between the number of equivalent oxygen sites increasing and the lattice free volume reducing with calcium content.